Differences in Larval Microhabitat Between Two Cryptic, Sympatric Salamander Species (Desmognathus folkertsi and D. amphileucus) in Northeastern Georgia, USA - Carlos D. Camp; Erick M. Fortner (Animals)
Sympatric species often exhibit habitat differences that promote coexistence. Two cryptic, sympatric salamander species, Desmognathus folkertsi and D. amphileucus, occupy streams across the Appalachian Mountains of northeastern Georgia, USA. Although frequently occurring together, the adults exhibit differences in microhabitat with D. folkertsi predominating in smaller streams and D. amphileucus more abundant in larger streams. Our purpose was to test for possible differences in larval habitat. Using a stream in which the two species coexist, we collected larvae from riffles, and biotic and abiotic variables associated with the stream and adjacent riparian zone were recorded. Because adults partially segregate by stream size, we noted the entry of a tributary that increased stream size and flow rate. Results showed a significant distribution of the two species upstream compared to downstream of the tributary, with no D. amphileucus found upstream; D. folkertsi was found throughout the study stream. We also found a significant difference between species in flow rate. We found no differences in any other variable that explained larval distribution patterns. We hypothesize that D. folkertsi nest in lower-flow riffles than D. amphileucus, resulting in the distribution of larvae, a pattern that may reflect selection on larval survival.